SISTEM PENDUKUNG KEPUTUSAN PENJUALAN BUKU MENGGUNAKAN METODE TREND MOMENT - Sopiah, Nyimas; Suyanto, Suyanto (JURNAL ILMIAH MATRIK, 2012)
An attempt to support education in our country the business of selling books. Sales of the book is very helpful for the buyer in this case students and students in completing the references to follow the lessons in school or college on campus. Thus a book stores hould be serious in managing his inventory so that it can serves hoppers well. Especially in the provision of books, a book store should carefully take into account the stock of books that should be fulfilled. There fore required a decision support system to assist decision makers in providing books. This research on decision support system sto build book sales by applying Trend Moment. The method used in this studyis descriptive, where as the software development method using the Re-Usable. Keywords: Systems, Decision Support, Sale, Trend Moment.